2012
DOI: 10.1111/j.1475-097x.2012.01148.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise prescription on daily physical activity and maximal exercise capacity in coronary artery disease patients with and without type 2 diabetes

Abstract: Summary Background Promotion of and adherence to increased physical activity (PA) is an important part of the prevention and treatment of coronary artery disease (CAD). We hypothesized that individually tailored home‐based exercise prescriptions will increase long‐term PA and maximal exercise capacity among CAD patients without and with type 2 diabetes (CAD+T2D). Methods Physical activity of patients with CAD (n = 44) and CAD+T2D (n = 39), matched by age, sex and ejection fraction, was measured over 5 days wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…In nonobese subjects a high-fish diet decreased TRL apoB48 concentration by reducing the secretion rate and the fractional catabolic rate of apoB48 135 . Omega-3 fatty acid supplementation significantly reduced mean fasting and postprandial TG 136 and accelerated chylomicron TG clearance by increasing LPL-mediated lipolysis 137 . Two new formulations of omega-3 fatty acids (AMR101 and an ultrapure mixture of free fatty acid forms of eicosapentaenoic acid [EPA] and docosahexaenoic acid [DHA]) are under clinical development and may provide additional TG-lowering effects by reducing VLDL production and increasing their catabolism thus potentially affecting also postprandial lipemia.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%
“…In nonobese subjects a high-fish diet decreased TRL apoB48 concentration by reducing the secretion rate and the fractional catabolic rate of apoB48 135 . Omega-3 fatty acid supplementation significantly reduced mean fasting and postprandial TG 136 and accelerated chylomicron TG clearance by increasing LPL-mediated lipolysis 137 . Two new formulations of omega-3 fatty acids (AMR101 and an ultrapure mixture of free fatty acid forms of eicosapentaenoic acid [EPA] and docosahexaenoic acid [DHA]) are under clinical development and may provide additional TG-lowering effects by reducing VLDL production and increasing their catabolism thus potentially affecting also postprandial lipemia.…”
Section: Omega-3 Fatty Acidsmentioning
confidence: 99%
“…Nevertheless, further scientific evaluation is called for in these reviews. There are different prescribed PA models from Denmark [ 16 ], the Netherlands [ 17 ], and Finland [ 18 ] and they all, just like the ERS’, vary in construct to some extent. The Swedish physical activity on prescription (PAP) model has five components: (a) patient-centred counselling, (b) written prescription of individualised PA using (c) the text book FYSS ( Physical Activity in the Prevention and Treatment of Disease ) for evidence-based prescriptions [ 19 ], (d) follow-up assessments, and (e) collaboration with societal organisations [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, further scientific evaluation of effects on HRQoL of the Swedish PAP model is needed as the literature is scarce [ 25 ]. Additionally, evaluation of the effects on health of different models for prescribing PA is needed as the international literature is inconclusive [ 13 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…22 For those who do begin a CR program, predictors of not completing include increased baseline depression 23 and hopelessness. 24 As a supplement or alternative to phase 2 CR, home-based exercise prescriptions promote physical activity and improve exercise capacity in patients with CHD, 25 and have been found as effective as phase 2 CR in improving exercise capacity, risk factor control, and health-related quality of life. 26 A meta-analysis of 12 studies showed no differences in either short-or long-term outcomes between patients with stable CHD participating in home-or hospital-based CR.…”
mentioning
confidence: 99%